Restoring mitophagy in prostate cancer cells: the role of miR-141 rescue in counteracting MAPK1/ERK2-dependent autophagy suppression - Radostina Tsvetankova; Ilka Tsvetkova; Soren Hayrabedyan; Krassimira Todorova (Biotechnology & Biotechnological Equipment)
Prostate cancer (PCa) stands as one of the most prevalent malignancies in men, ranking as the fifth leading cancer-associated mortality. Castration-resistance metastatic phenotype acquisition is substantiated by reprogramming of cellular responses to oxidative stress damage, involving evading apoptosis by losing p53 and modulating canonical mitophagy. Understanding the molecular underpinnings of mitochondria-related PCa, dysregulated miR-141 and autophagy-modulating MAPK1/ERK2 in canonical mitophagy altered context of PCa cell line model (LNCaP (p53+/+) and PC3 (p53−/−)) can provide insights into potential therapeutic strategies. Utilising nanopore transcriptome sequencing, differential gene expression was analysed post miR-141 mimic/inhibitor modulation. MiR-141 upregulation enriched pathways associated with TAK1-JNK-c-Jun and MAPK activation. However, its inhibition prioritized non-immune pathways, emphasising lysosome biogenesis. Using DAPGreen (a microtubule-associated protein 1A/1B-light chain 3 (LC3) marker analogue), flow cytometry and live imaging demonstrated that miR-141 rescue amplified macroautophagy in p53+/+ cells, which diminished under starvation; conversely, in p53−/− cells, the rescue initially suppressed macroautophagy but enhanced it when combined with starvation. MAPK1 silencing revealed that MAPK1 had suppressive effect in p53+/+ cells, which was lost in p53−/− cells. Combined with starvation it resulted in macroautophagy upregulation in both cell lines. Mitophagy flux detected by MtPhagy and Lyso dyes demonstrated that miR-141 rescue amplified mitophagy under normal and starved conditions in p53+/+ cells, while in p53−/− cells, amplification only occurred during starvation. In both cell lines, starvation alone supressed mitophagy. MAPK1 had suppressive effect on mitophagy only during starvation, regardless of p53 status. Modifying miR-141 and MAPK1/ERK2 dynamic duality axis could present a potential therapeutic strategy.